Characterization of biodegradable polymers irradiated with swift heavy ions - Salguero, N. G. (2012)
In view of their application as biomaterials, there is an increasing interest in developing new methods to induce controlled cell adhesion onto polymeric materials. The critical step in all these methods involves the modification of polymer surfaces, to induce cell adhesion, without changing theirs degradation and biocompatibility properties. In this work two biodegradable polymers, polyhydroxybutyrate (PHB) and poly-L-lactide acid (PLLA) were irradiated using carbon and sulfur beams with different energies and fluences. Pristine and irradiated samples were degradated by immersion in a phosphate buffer at pH 7.0 and then characterized. The analysis after irradiation and degradation showed a decrease in the contact angle values and changes in their crystallinity properties.